2019
DOI: 10.1002/prca.201900018
|View full text |Cite
|
Sign up to set email alerts
|

Management of Tamm–Horsfall Protein for Reliable Urinary Analytics

Abstract: PurposeUrinary extracellular vesicles (uEVs) are a novel source of biomarkers. However, urinary Tamm–Horsfall Protein (THP; uromodulin) interferes with all vesicle isolation attempts, precipitates with normal urinary proteins, thus, representing an unwanted “contaminant” in urinary assays. Thus, the aim is to develop a simple method to manage THP efficiently.Experimental designThe uEVs are isolated by hydrostatic filtration dialysis (HFD) and treated with a defined solution of urea to optimize release of uEVs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 41 publications
0
33
1
Order By: Relevance
“…Clinical biomarker studies should, therefore, attempt to validate biomarker detection in urine collected without prior DRE, given this does not negatively influence detection sensitivity [67]. The treatment of urine or uEV with the reducing agent dithiothreitol (DTT), zwitterionic detergent CHAPS or urea to denature and remove abundant THP has previously been proposed [68–70]. However, this study demonstrated no significant advantage of DTT treatment on reducing THP contamination or increasing uEV yield when applying a BU ODG.…”
Section: Discussionmentioning
confidence: 97%
“…Clinical biomarker studies should, therefore, attempt to validate biomarker detection in urine collected without prior DRE, given this does not negatively influence detection sensitivity [67]. The treatment of urine or uEV with the reducing agent dithiothreitol (DTT), zwitterionic detergent CHAPS or urea to denature and remove abundant THP has previously been proposed [68–70]. However, this study demonstrated no significant advantage of DTT treatment on reducing THP contamination or increasing uEV yield when applying a BU ODG.…”
Section: Discussionmentioning
confidence: 97%
“…However, as our focus was on RNA sequencing, we did not include any further purification step. As a reference, HFD in combination with protocols to reduce THP interference has been successfully used for uEV proteomics (Hu et al., 2018; Xu et al., 2019). The UC protocol presented in our study has not been used for proteomics, but UC in combination with reducing agents such as DTT (Rood et al., 2010; Wolley et al., 2017), or sucrose gradient centrifugation (Hogan et al., 2014), or size exclusion chromatography (Rood et al., 2010) have been used for uEV proteomics with good results.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the high variation of EV recovery due to inter-day urine collection seems to be hampered by the addition of protease inhibitors [ 148 ]. Unfortunately, the optimal inhibitor cocktail is still an open debate with several authors showing that different protease inhibitor cocktails had different impacts on the ratio of THP polymerization and consequently on the yield of urinary EVs in the UC pellets [ 148 , 151 , 152 , 153 ].…”
Section: Extracellular Vesicles From Liquid Biopsies As a Source Omentioning
confidence: 99%